2022
DOI: 10.3390/membranes12080761
|View full text |Cite
|
Sign up to set email alerts
|

Efficiencies of O-MBR and A/O-MBR for Organic Matter Removal from and Trihalomethane Formation Potential Reduction in Domestic Wastewater

Abstract: Lab-scale anoxic/oxic membrane bioreactor (A/O-MBR) and oxic membrane bioreactor (O-MBR) systems using a submerged polysulfone hollow-fiber membrane module with a pore size of 0.01 μm and a total surface area of 1.50 m2 were used to treat domestic wastewater. The sludge retention time (SRT) of each system was examined by setting the SRT to 10, 20, and infinity (no sludge withdrawal). The results showed that the total nitrogen removal efficiency of the A/O-MBR was more significant than that of the O-MBR at a SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For full-scale implementation of the systems, it is expected that AeMBR and AnMBR performance could be significantly improved ( e.g. , 80–90% COD removal as reported in the literature 26 ) via design optimization ( e.g. , longer SRT).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…For full-scale implementation of the systems, it is expected that AeMBR and AnMBR performance could be significantly improved ( e.g. , 80–90% COD removal as reported in the literature 26 ) via design optimization ( e.g. , longer SRT).…”
Section: Resultsmentioning
confidence: 91%
“…[32][33][34] Environmental Science: Water Research & Technology Paper lowest effluent COD levels were observed when TS-IOBAC was applied downstream of an aerobic bioreactor, which were consistently lower than 150 mg L −1 by the last 2 weeks of the 4-week experiment. For full-scale implementation of the systems, it is expected that AeMBR and AnMBR performance could be significantly improved (e.g., 80-90% COD removal as reported in the literature 26 ) via design optimization (e.g., longer SRT). Although design iterations upstream of the TS-IOBAC system were outside the scope of this study, there is a wealth of literature on the design and performance of membrane bioreactors [27][28][29][30][31][32] including the potential for methane recovery from AnMBR and characterization of fugitive gaseous emissions 30,31 that can be considered in the scale-up of an integrated MBR and TS-IOBAC system.…”
Section: Ts-iobac As a Post-secondary Polishing Processmentioning
confidence: 92%
“…The process can be designed to handle a wide range of wastewater characteristics, including high-strength and low-strength wastewater. This flexibility allows the MBR process to be used in a wide range of applications, from small-scale decentralized systems to large municipal wastewater treatment plants [16,19]. MBR has been shown to achieve high removal rates for suspended solids, biological oxygen demand (BOD), total nitrogen (TN), and total phosphorus (TP).…”
Section: 2membrane Bioreactor (Mbr) Processmentioning
confidence: 99%